Gaeolaelaps scarites sp. nov., a new laelapid mite (Acari: Mesostigmata) associated with Scarites terricola (Coleoptera: Carabidae) from Iran. Issue 3 (3rd April 2019) - Saeidi, Shahram; Maroufpoor, Mostafa; Hajiqanbar, Hamidreza; Joharchi, Omid
ABSTRACT: A new mite species of the genus Gaeolaelaps, G. scarites Joharchi and Saeidi sp. nov., collected from under the elytra and on the abdomen of Scarites ( Parallelomorphus ) terricola Bonelli (Coleoptera: Carabidae) in Iran is described and illustrated. http://www.zoobank.org/urn:lsid:zoobank.org:pub:2C885CB5-1DDB-4C25-8E81-01287CA9E38E http://www.zoobank.org/urn:lsid:zoobank.org:act:75DF6728-D54A-417E-B644-5C8B16633AF2